Occupational Therapy Interventions Effect on Visual-Motor Skills in Children with Learning Disorders - Batoul Mandani; Ali Hossein Sazmand; Mozhgan Farahbod; Masoud Karimlou; Mashaallah Mandani (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: Visual-motor skill is a part of visual perception which can integrate visual processing skills to fine movements. Visual-motor dysfunction is often to cause problems in copying and writing. The purpose of this study is investigation of occupational therapy interventions effect on the visual-motor skill in children with learning disorders. Materials & Methods: In this interventional and experimental study, 23 students with learning disorders (2nd, 3rd, 4th grade) were selected and they were divided (through Randomized Block Method) into two groups, 11 persons as intervention group and the others as the control group (12 people). Both groups were administered the "Test of Visual-Motor Skills- Revised" (TVMS-R). Then case group received occupational therapy interventions for 16 sessions and two groups were administered by TVMS-R again. Data was analyzed by using paired T-test and independent T-test. Results: Total mark of TVMS-R demonstrated statistically significant difference in visual-motor skills between case and control groups (P<0/001). This test has 8 categories. Total mark of 1, 3,4,6,8 categories demonstrated that occupational therapy had significant effect on visual analysis skills (P<0/005). Total mark of 2, 5, 7 categories demonstrated that occupational therapy had significant effect on visual-spatial skills (P<0/001). Conclusion: Occupational therapy interventions had significant effect on the visual-motor skills and its items (visual-spatial, visual analysis, visual-motor integration and eye fixation skills).